1997
DOI: 10.1634/theoncologist.2-3-153
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Involvement and the Role of Prophylactic Cranial Irradiation in Small Cell Lung Cancer

Abstract: This paper studies the frequency and manifestations of central nervous system (CNS) involvement and assesses the role of prophylactic cranial irradiation in small cell lung cancer (SCLC). All patients with confirmed diagnosis, admitted to our department within the last 15 years, were included. Patients were staged as having limited or extensive disease. Irradiation (40 Gy/20f) was offered to all complete responders immediately after polychemotherapy. There were 200 patients (176 men and 24 women, median age 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…PCI is effective in reducing the incidence of brain metastasis of SCLC. Several randomized studies showed that PCI reduced the rate of brain metastases in the patients with SCLC who achieved CR [ 10 , 24 , 25 ].Our meta-analysis also revealed that PCI reduced the incidence of brain metastasis within one year, with a pooled relative risk of 0.45 (95% CI, 0.35 to 0.58; P < 0.00001). Combining with previous studies, we concluded that PCI reduced the incidence of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…PCI is effective in reducing the incidence of brain metastasis of SCLC. Several randomized studies showed that PCI reduced the rate of brain metastases in the patients with SCLC who achieved CR [ 10 , 24 , 25 ].Our meta-analysis also revealed that PCI reduced the incidence of brain metastasis within one year, with a pooled relative risk of 0.45 (95% CI, 0.35 to 0.58; P < 0.00001). Combining with previous studies, we concluded that PCI reduced the incidence of brain metastases.…”
Section: Discussionmentioning
confidence: 99%